Assessing Threshold Levels Of Income Inquality And Human Development Quality On Economic Growth In Indonesia - Cahyadin, Malik; Tambunan, Tulus T.H. (Universitas Bengkulu, 2025)
Abstract This study attempts to assess threshold levels of income inequality and human development quality on economic growth for 34 provinces in Indonesia during 2022-2023. The cross-section threshold regression was employed. The findings reveal that the threshold levels of income inequality in 2022 and 2023 were 0.319 and 0.345, respectively. At the same time, the threshold levels of human development index were 71.65 and 71.25, respectively. The condition posits that the quality of income distribution and human development will be marginally lower in 2023 than in 2022. By considering Global OLS, total labor force and unemployment rate deliver a significant and negative impact on economic growth at 10% level in 2022. Interestingly, FDI provides a positive impact at 10% (income inequality) and 1% (human development) levels. Therefore, the central and local governments are challenged to design economic development under inclusive and sustainable perspectives. Their policies can improve the quality of labor (educated, skilled labors, and productive) and increase the equality of economic activities for all provinces. Besides, those governments should lead all economic agents to obtain and guarantee the quality of human development in the long-run. Keywords : Income Inequality, Human Development, Threshold Level, Economic Growth. Abstrak Studi ini berupaya menilai ambang batas ketimpangan pendapatan dan kualitas pembangunan manusia terhadap pertumbuhan ekonomi di 34 provinsi di Indonesia selama periode 2022–2023. Metode cross-section threshold regression digunakan dalam analisis ini. Temuan penelitian menunjukkan bahwa ambang batas ketimpangan pendapatan pada tahun 2022 dan 2023 masing-masing sebesar 0,319 dan 0,345. Pada saat yang sama, ambang batas indeks pembangunan manusia (IPM) masing-masing tercatat sebesar 71,65 dan 71,25. Kondisi ini menunjukkan bahwa kualitas distribusi pendapatan dan pembangunan manusia pada tahun 2023 sedikit lebih rendah dibandingkan dengan tahun 2022. Dengan mempertimbangkan Global OLS, total angkatan kerja dan tingkat pengangguran memberikan pengaruh yang signifikan dan negatif terhadap pertumbuhan ekonomi pada taraf 10% di tahun 2022. Menariknya, Penanaman Modal Asing memberikan dampak positif pada taraf 10% (untuk ketimpangan pendapatan) dan 1% (untuk pembangunan manusia). Oleh karena itu, pemerintah pusat dan daerah ditantang untuk merancang pembangunan ekonomi dengan perspektif yang inklusif dan berkelanjutan. Kebijakan mereka dapat meningkatkan kualitas tenaga kerja (terdidik, terampil, dan produktif) serta mendorong pemerataan aktivitas ekonomi di seluruh provinsi. Selain itu, pemerintah juga perlu memimpin seluruh pelaku ekonomi untuk mencapai dan menjamin kualitas pembangunan manusia dalam jangka panjang. Kata kunci: Ketimpangan Pendapatan, Pembangunan Manusia, Tingkat Ambang, Pertumbuhan Ekonomi